Legacy phosphorus in Brazilian agriculture and cover crops contribution to enhance this nutrient bioavailability in tropical Oxisols - Rodrigues, Marcos (2018)
Phosphorus (P) one of the essential elements to plants and animals, is a non-renewable resource and accuatlly high demanded in agriculture. The World\'s population growth and future estimatives on food demands raises the question about the sustainability of the current agriculture systems, speccially concerns about the low P use efficiency in agroecosystems. Brazilian agriculture requires high P inputs and many researches has been developed to increase the crops yield and, consequently, food production efficiency. However, this development was achieved at the high costs of mineral fertilisers (specially P) and long-term perspectives about the costs of the intensification in the tropical agriculture is accuattly in debate. In this conxtext, in the present thesis chapter two we evaluated the evolution of the Brazilian cropland basis and P demands, quantifying the Brazil P Legacy and, based on scenarios involving the cropland area and yield expansion, we estimated the future (up to 2050) Legacy P and P fertilisers demand. We also estimated the potential aleviation that could be achieved in the mineral fertilizers consumption by utilisation and improvements on manure P recycling. Alternatively, considering the systems intensification and its effects on P availability, we proposed alternative scenarios to promote the Legacy P utilisation in Brazil\'s improved agriculture systems to grant the agriculture expansion without huge increments on the national P fertilisers consumption. A worldwide recognized advance in Brazilian agriculture is the Cerrado, where large cropland areas accually are cultivated twice a year, improving the food and fiber production without any additional disturbance of natural ecossystems. In this context, no-tillage (NT) agriculture has been widely used and, as consequence, soil fertility has been improved, which could be also farorable to the P availability, when rotation with crop species with P mobilization mechanisms are introduced, such as cover crops utilisation. However, the effects of these improved rotated systems on P bioavailability in long-term in tropical soils remains uncert in the literature and was our objective in the chapter three, where is described a study envolving the evaluation of long-term changes on P fractions in tropical Oxisols, from two long-term field trials involving tillage systems (NT and conventional tillage, CT) and cover crops (millet, brachiaria, maize and control, fallow). The long-term cultivation generated large amounts of legacy P in the soil and with the brachiaria introduction as cover crop, more P was recycled in the topsoil and labile P and all the organic P fractions increased. Based on the cover crop effects, we proposed that the bioavailability of the legacy P could be represented by the P extracted by the labile fractions + moderately labile P fractions. In the chapter four, we used other techniques actually widely applied to P speciation, and we applied in tropical soils affected by the native Cerrado conversion into NT and CT agriculture. A multiple approach to identify and quantify the P forms in tropical soils were proposed by the utilisation of Hedley\'s fractionation togheter with P K-edge XANES for P-bindings into inorganic soil matrix and liquid 31P-NMR spectroscopy to complement the organic P species in tropical soils.